SOFSEM 2020 : Theory and Practice of Computer Science : 46th International Conference on Current Trends in Theory and Practice of Informatics, SOFSEM 2020, Limassol, Cyprus, January 20-24, 2020, Proceedings /: Theory and Practice of Computer Science : 46th International Conference on Current Trends in Theory and Practice of Informatics, SOFSEM 2020, Limassol, Cyprus, January 20-24, 2020, Proceedings. (2020) - Unknown
No abstract available